Associations of pregnancy-associated plasma protein-A level with essential hypertension and hypertensive disorders in pregnancy in Chinese population: a meta-analysis of 20 research studies involving 3332 individuals. Issue 9 (28th September 2015) - Cai, Gaojun; Zhang, Bifeng; Weng, Weijin; Yang, Liping; Shi, Ganwei; Xue, Sheliang; Fu, Xingli
Abstract : Objective: To explore the associations between serum pregnancy-associated plasma protein-A (PAPP-A) level, and essential hypertension (EH) and hypertensive disorders in pregnancy (HDP) in Chinese population. Methods: Pertinent studies were independently searched in PubMed, Embase, Cochrane Library, Chinese Biomedical Database (CBM), Wanfang databases and China National Knowledge Infrastructure (CNKI). The standardised mean difference (SMD) with 95% CIs was used to estimate the size of the effect. The subgroup analyses and meta-regression analysis were performed to identify the sources of heterogeneity among studies. Sensitivity analysis was conducted to assess the stability of the results. The publication bias between studies was examined by using Begg's funnel plots and Egger's test. Results: A total of 20 studies involving 1493 patients and 1839 controls were included in the current meta-analysis. The PAPP-A level was significantly higher in EH patients than in controls (SMD=1.960, 95% CI 1.305 to 2.615, p<0.001), and significant associations were observed in all subgroups. The PAPP-A level was also significantly higher in HDP patients than in healthy pregnant women (SMD=2.249; 95% CI 1.324 to 3.173, p<0.001). The positive association between PAPP-A level and the risk of HDP was consistently observed in all subgroups except the subgroup with low NOS score. Conclusions: The present meta-analysis suggests that an elevated PAPP-A level may be associated with susceptibilities to EH and HDP.